Multiple observations of the sea anemone Phyllodiscus semoni Kwietniewski, 1897 (Actiniaria: Aliciidae) from Sabah, Borneo represent first records for Malaysia - Sancia E.T. van der Meij; Stefano G.A. Draisma; Zarinah Waheed (Elsevier, 2018)
The stinging sea anemone Phyllodiscus semoni is recorded from Malaysia for the first time. This species exhibits high morphological variation, and morphotypes resembling dead coral rock, soft and stony corals and algae have been documented. Correct identification and information on local occurrences of Phyllodiscus is important, since this species is armed with venom-laden nematocysts that are hazardous to humans. In situ photographs ofthe specimens encountered in Malaysian Borneo are provided and their morphotypes are discussed.